Morphogenetic variability during selection of elite water polo players - Cvjeticanin, S.; Marinkovic, D. (Journal of Sports Sciences, 2009)
In this population-genetic study, we compared morphological and genetic variability of a control group of individuals with that of developing and elite water polo players from Serbia, using a test of determination of homozygously recessive characteristics in humans (HRC-test). Comparisons of the frequencies of ABO and Rh blood types were also made for the groups examined. The degree of genetic homozygosity showed not only statistically significant differences in the mean values obtained for the studied samples (control group 5.1 ± 0.2; emerging water polo players 3.5 ± 0.1; elite water polo players 1.9 ± 0.3 HRCs, out of 20 analysed characteristics), but also differences in the type of distribution, as well as the presence of specific combinations of such traits. During identification of swimming talents, the degree of genetic homozygosity showed a significant decrease, from 4.8 ± 0.3 in the group of pre-competitive young boys, to 2.7 ± 0.3 in selected adult team members, to only 1.9 ± 0.3 in elite water polo players. In the group of pre-competitive young individuals, all characteristics tested also had homo-recessive combinations, while in the group of elite water polo players only 8 of 20 traits were expressed as homozygously recessive. In the group of elite water polo players, who were World and European champions as well as Olympic champions, the frequencies of the A and B blood types were low, AB was absent, and the frequency of the O blood type was high at 72.2 % (i.e. almost twice the expected percentage).